Effects of intermittent hypoxia exposures and interval hypoxic training on exercise tolerance (narrative review) - J. Burtscher; O. S. Glazachev; M. Kopp; M. Burtscher (Спортивная медицина: наука и практика, 2024)
The ability to perform steady-state submaximal exercise at a certain intensity (exercise tolerance) predicts endurance performance in athletes, but also the quality of life and the capability to perform daily living activities in older people and patients suffering from chronic diseases. Improvements in exercise tolerance following exercise training are well established but may also occur or be enhanced as a consequence of adaptations to other stimuli, e.g., repeated exposures to real or simulated altitude. Adaptive responses (i.e., beneficially impacting exercise tolerance) depend on the type and extent of hypoxia stimuli, in particular, whether they are applied during exercise (intermittent hypoxia training, IHT) or at rest (intermittent hypoxia exposure, IHE).This brief review summarizes the evidence showing that IHT seems to elicit more pronounced effects on exercise tolerance than IHE. The most relevant adaptations to IHT are primarily provoked within the working skeletal muscles, whereas the rather small effects of IHE may include improved autonomic regulatory processes, endothelial function, cardioprotection, and increasing antioxidant capacity, all of which can probably be enhanced by combination with exercise (IHT). While IHE seems particularly suited for sedentary and elderly people or those suffering from chronic diseases, IHT will be more appropriate for young and already trained people. Thus, IHE is recommended for those with low exercise tolerance and can be followed up with exercise training in normoxia and finally with IHT.